Development and ontogenetic changes of feeding behaviour during juvenile early growth of Eupolymnia nesidensis (Annelida, Terebellidae). Issue 2 (3rd April 2022) - Toso, Andrea; Giangrande, Adriana
ABSTRACT: Reproduction of the terebellid Eupolymnia nesidensis was investigated in a population from the Ionian Sea (Mediterranean, South Italy). This species has a worldwide distribution and is very common on Mediterranean hard substrata covered by algae. Observations revealed a spawning period across springtime with lecithotrophic development occurring inside a jelly mass, with eggs measuring 210 μm in diameter. Juveniles leave the jelly mass after 12–13 days building a transitory tube and exhibiting a vagile benthic behaviour, incorporating food directly through the mouth opening. During the juvenile stage, at day ~100, an ontogenetic shift related to feeding behaviour was observed. Specifically, the vagile feeding behaviour was replaced by the adult feeding strategy with the use of the fully developed head tentacles.